THE CULTURAL ENACTMENT OF EVIL EYE: AN ETHNOGRAPHY OF STRANGE POWER AND WELL-BEING - NIMRA AROOJ (Innovare Journal of Social Sciences, 2025)
This paper explores the cultural enactment of the evil eye (nazar) within Pakistani society, analyzing its significance as a symbol of both protection and social well-being. Drawing from a personal narrative that illustrates the profound impact of nazar beliefs on family dynamics and health, the study employs Clifford Geertz’s interpretive anthropology as a framework for understanding the intricate rituals, amulets, and linguistic expressions associated with this phenomenon. Through ethnographic methods, including participant observations and narratives, the research highlights how practices such as the burning of chillies and the use of black amulets serve not only as remedies for perceived malevolent forces but also as mechanisms for fostering psychological comfort and social cohesion. The findings reveal that the belief in the evil eye transcends mere superstition; it is a vital cultural construct that helps individuals navigate envy, maintain harmony, and promote overall well-being within their communities. This investigation underscores the enduring relevance of cultural symbols in shaping human experiences and reinforcing communal bonds.